Microwave drying kinetics of okra - Dadali, Gokce; Apar, Dilek Kilic; Ozbek, Belma (TAYLOR & FRANCIS INC, 2007)
In this work, the effects of power level and sample mass on moisture content, moisture ratio, drying rate, and drying time of Turkey okra (Hibiscus esculenta L.) were investigated using microwave drying technique. Various microwave power levels ranging from to 180 to 900 W were used for drying of 100 g of okra. To investigate the effect of sample mass on drying, the samples in the range of 25 to 100g were dried at microwave power level of 360 W. To determine the kinetic parameters, the drying data were fitted to various models based on the ratios of the differences between the initial and final moisture contents and equilibrium moisture content. Among of the models proposed, Page's model gave a better fit for all drying conditions used. The activation energy for microwave drying of okra was calculated using an exponential expression based on Arrhenius equation and was found to be 5.54 W/g.
Keywords: drying kinetic; microwave drying; minimum energy; okra; DESORPTION ISOTHERMS; LAYER; QUALITY; CARROT; AIR; DEHYDRATION; PARAMETERS; APPLE; HEAT; Engineering